If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 4 = 5x + -3 Reorder the terms: 4 + 8x = 5x + -3 Reorder the terms: 4 + 8x = -3 + 5x Solving 4 + 8x = -3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 4 + 8x + -5x = -3 + 5x + -5x Combine like terms: 8x + -5x = 3x 4 + 3x = -3 + 5x + -5x Combine like terms: 5x + -5x = 0 4 + 3x = -3 + 0 4 + 3x = -3 Add '-4' to each side of the equation. 4 + -4 + 3x = -3 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = -3 + -4 3x = -3 + -4 Combine like terms: -3 + -4 = -7 3x = -7 Divide each side by '3'. x = -2.333333333 Simplifying x = -2.333333333
| 2r=6.02 | | 6/45=10/y | | A=3(15-5) | | 5-x=38 | | c-36=29 | | y+7.53=19.83 | | 3h+4h-(-11h)-18h-2h=8 | | 6+m=42 | | -2x-2=(-16) | | 11=s-2 | | Y+8=4y | | 5r-12=38 | | 12/16=18/w | | y-17=x | | d+1=3.34 | | 32a+91=124 | | 140=10x+15y | | 3y+17=44 | | 5x-8=11-12x | | 2f=3.6 | | x^3-5x+x=5 | | C=12*4+8 | | 8h-4h-14h=20 | | 5y-(2y-10)=25-5y+7 | | c=48d+8 | | 2a-16=14 | | 11j+3j+(-7j)+(-8j)=13 | | 15=3(d+1)+6 | | (9+z)(3z-7)=0 | | =7x+8-6x | | 9+2(x-13)=45 | | 7x-34=5x |